Education, culture and environmental citizenship program to raise awareness among the population of Ventanilla in Lima, Peru (LACCEI, 2024)
The lack of environmental education and culture in the population generates actions against the environment. Therefore, each local government is responsible for preserving and promoting the conservation of ecosystems. Thus, the objective of this research was to evaluate the annual work plan of a municipal program of education, culture and environmental citizenship (EDUCCA), carried out in the years 2018 to 2020 in the district of Ventanilla in Lima, Peru. For the evaluation, a documentary review of all the activities raised and executed in the work plans of the years under study was carried out. Tests and surveys conducted by the district municipality of Ventanilla were also reviewed. The study indicated that, in 2019 there were better results compared to 2018 and 2020, training 107 school environmental promoters (SEP), 35 youth environmental promoters (YEP) and 78 community environmental promoters (CEP). In the same year, 5 events and 5 campaigns on environmental issues were held, observing greater interest from respondents in answering questions related to environmental issues and knowledge of the program. Finally, it is concluded that the municipal program EDUCCA promotes environmental education and culture among citizens, and serves as a model for other public entities to improve their environmental management policies.